Motor vehicles, the environment, and the human condition driving to extinction - Baer, Hans A., 1944- (Environment and society., 2019)
"The world now has more than a billion motor vehicles, and this number continues to increase as developing countries imitate developed societies in their adoption of the culture of automobility. Motor Vehicles, the Environment, and the Human Condition: Driving to Extinction explores the political ecology of motor vehicles in an era of growing social disparities and environmental crises, the latter of which are most manifest in anthropogenic climate change to which motor vehicles are a major contributor. A political, ecological perspective recognizes that motor vehicles, perhaps more than any other machine, embody the social, structural, cultural, and environmental contradictions of the capitalist world system. In addition to highlighting many of the environmental, social, and health consequences of humanity's increasing reliance on motor vehicles, particularly private automobiles, this book argues that, ultimately, as a species we need to move beyond motor vehicles as much as possible. However, such an effort will have to be part and parcel of creating an alternative world system based on social justice, democratic processes, environmental sustainability, and a safe climate, one termed democratic eco-socialism"--Back cover.